The study of harmonic distortion in Faculty of Electrical Engineering / Mohd Zakuan Mohd Kamaluddin - Mohd Kamaluddin, Mohd Zakuan (2013)
This paper presents the power quality problems on the distribution system of faculty electrical engineering (FEE). The power quality problem in this paper is to finds out about the harmonic distortions. Firstly, Ion Meter 7330 is used to measure the entire harmonic distortion for the whole building of FEE. Then, the building was audited to analyses the equipment that involves the harmonic distortion. After that, the measurement of equipment largely use in FEE that produced large harmonic distortion was measured using a fluke meter. The measurement is taken for four days to make sure that the data taken more accurate. There are two equipments largely used in the FEE, one is computer and secondly is fluorescent light. The Matlab Simulink version 2010a was used to design and simulate the harmonic data from the actual data.